The Analysis of Differences in Patient Satisfaction Levels with Interprofessional-Based Emergency Services in Primary Care: Analysis of Differences in Patient Satisfaction Levels with Interprofessional-Based Emergency Services in Primary Care - Hafizullah, Ahmad (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Interprofessional-based emergency services in primary care have emerged as an innovative approach to improving healthcare quality. This study aims to analyze the differences in patient satisfaction levels between interprofessional-based emergency services and conventional models. A quantitative research approach with a descriptive analytical design was employed. Data were collected through questionnaires completed by 150 respondents from several primary Lubuk Pakam Community Health Center. The findings indicate that medical service quality, waiting time, interprofessional communication, empathy, and facility infrastructure play significant roles in determining patient satisfaction. Bivariate analysis revealed a significant relationship between medical service quality and waiting time with patient satisfaction levels (p < 0.05). The implementation of an interprofessional approach has been proven to enhance service coordination and overall patient satisfaction. Therefore, this model is recommended for broader application in primary care settings to improve healthcare service effectiveness.